An ∼600 pc View of the Strongly Lensed, Massive Main-sequence Galaxy J0901: A Baryon-dominated, Thick Turbulent Rotating Disk with a Clumpy Cold Gas Ring at z = 2.259 - Daizhong Liu; N. M. Förster Schreiber; R. Genzel; D. Lutz; S. H. Price; L. L. Lee; Andrew J. Baker; A. Burkert; R. T. Coogan; R. I. Davies; R. L. Davies; R. Herrera-Camus; et al. (The Astrophysical Journal, 2023)
We present a high-resolution kinematic study of the massive main-sequence star-forming galaxy (SFG) SDSS J090122.37+181432.3 (J0901) at z = 2.259, using ∼0.″36 Atacama Large Millimeter/submillimeter Array CO(3–2) and ∼0.″1–0.″5 SINFONI/VLT H α observations. J0901 is a rare, strongly lensed but otherwise normal massive ( $log(M_{\star }/M_{\odot })\sim 11$ ) main-sequence SFG, offering a unique opportunity to study a typical massive SFG under the microscope of lensing. Through forward dynamical modeling incorporating lensing deflection, we fit the CO and H α kinematics in the image plane out to about one disk effective radius ( R _e ∼ 4 kpc) at an ∼600 pc delensed physical resolution along the kinematic major axis. Our results show high intrinsic dispersions of the cold molecular and warm ionized gas ( σ _0,mol. ∼ 40 km s ^−1 and σ _0,ion. ∼ 66 km s ^−1 ) that remain constant out to R _e ; a moderately low dark matter fraction ( f _DM ∼ 0.3–0.4) within R _e ; and a centrally peaked Toomre Q parameter—agreeing well with the previously established σ _0 versus z , f _DM versus Σ _baryon , and Q 's radial trends using large-sample non-lensed main-sequence SFGs. Our data further reveal a high stellar mass concentration within ∼1–2 kpc with little molecular gas, and a clumpy molecular gas ring-like structure at R ∼ 2–4 kpc, in line with the inside-out quenching scenario. Our further analysis indicates that J0901 had assembled half of its stellar mass only ∼400 Myr before its observed cosmic time, and the cold gas ring and dense central stellar component are consistent with signposts of a recent wet compaction event of a highly turbulent disk found in recent simulations.